How a face may affect object-based attention: evidence from adults and 8-month-old infants - Valenza, Eloisa; Franchin, Laura; Bulf, Hermann (Frontiers in Integrative Neuroscience, 2014)
Object-based attention operates on perceptual objects, opening the possibility that the costs and benefits humans have to pay to move attention between objects might be affected by the nature of the stimuli. The current study reported two experiments with adults and 8-month-old infants investigating whether object-based-attention is affected by the stimulus social salience (faces vs. non-faces stimuli). Using the well-known cueing task developed by Egly et al. (1994) to study the object-based component of attention, in Experiment 1 adult participants were presented with two upright, inverted or scrambled faces and an eye-tracker measured their saccadic latencies to find a target that could appear on the same object that was just cued or on the other object that was uncued. Data showed that an object-based effect (a minor cost to shift attention within- compared to between-objects) occurred only with scrambled face, but not with upright or inverted faces. In Experiment 2 the same task was performed with 8-month-old infants, using upright and inverted faces. Data revealed that an object-based effect only emerges for inverted faces but not for upright faces. Overall, these findings suggest that object-based attention is modulated by the stimulus social salience and by the experience acquired by the viewer with different objects.